Enantioselective Synthesis of 4H‐Pyrans Through Organocatalytic Asymmetric Formal [3+3] Cycloadditions of 2‐(1‐Alkynyl)‐2‐alken‐1‐ones with β‐Keto Esters. Issue 19 (24th August 2016) - Yue, Zhenting; Li, Wenbo; Liu, Lu; Wang, Cuihong; Zhang, Junliang
Abstract: 4 H ‐Pyran units are frequently present in molecules with significant biological and pharmaceutical activities. Herein, we present the first enantioselective formal [3+3] cycloaddition between 2‐(1‐alkynyl)‐2‐alken‐1‐ones and β‐keto esters catalyzed by a cyclohexyldiamine‐based thiourea‐tertiary amine bifunctional catalyst. Under the mild and eco‐friendly conditions, a wide range of polysubstituted 4 H ‐pyrans were obtained in moderate yields with good enantioselectivities. Abstract :